Development of Teaching Effectiveness Scale for University Teachers - Shumaila Shahzad; Nasir Mehmood (National University of Modern Languages (NUML), Islamabad, 2021)
Effectiveness can be assessed in terms of achievability of objectives. Teaching process at higher education level aims at students' cognitive, psychomotor and effective development so that university graduates could become effective members of society after completion of their studies. Purpose of education can never be achieved without teachers. It can safely be said that effectiveness of education system largely depends on effectiveness of its teachers. Accountability or teacher evaluation helps ensure teaching effectiveness. Therefore, this study aimed at construction of such a scale which could be used to assess university teachers' teaching effectiveness. For preparing Teaching Effectiveness Scale (TES), primarily, 65 statements were prepared as an item pool after literature review related to capabilities of efficient and effective teacher. Items were extracted from literature review (i.e., contemporary scales for teacher evaluation), informal interviews with ten university teachers and focus group discussions with three intact groups of graduates were held. Later on, 16 Subject Matter Experts (SMEs) judged the content validity. Content Validity Index (CVI) and Content Validity Ratio (CVR) were calculated to retain 43 content valid items. Finally, these 43 items were administered to 698 university students. Confirmatory Factor Analysis (CFA) was performed on LISREL 8.8. to ensure construct validity. Finally, there remained 32 items whose factor loadings were more than 0.40. Reliability Coefficient Value (RCV) was high (r= 0.87). In this way, TES comprised four sub scales i.e. (a) Classroom Management (CM), (b) content and pedagogical skills, (c) Facilitative Classroom Environment (FCE) and (d) Student Teacher Relationship (STR). The scale possesses high psychometric properties and is available for use.